Disorders of puberty. (September 2021) - Hendriks, Emile; Prentice, Philippa; Williams, Rachel
Abstract: Puberty is the process of development of adult secondary sexual characteristics. Disorders of puberty can be classified into early (precocious) and late (delayed) puberty. Early (precocious) puberty can be secondary to either activation of the hypothalamo–pituitary–gonadal axis (gonadotrophin dependent, or central) or altered regulation of sex hormone production in the gonads, adrenal glands or other tissues (gonadotrophin independent or peripheral). Delayed puberty is most often constitutional, but hypogonadotropic (central) and hypergonadotropic (peripheral) hypogonadism should be considered. This article discusses the clinical and biochemical features of normal and abnormal puberty.